Empowering the family during the first months after identification of permanent hearing impairment in children. - Ciciriello, E; Bolzonello, P; Marchi, R; Falzone, C; Muzzi, E; Orzan, E (Acta Otorhinolaryngol Ital, 2016)
The latest international guidelines highlight the importance of involving the family in the diagnostic and rehabilitation process of children affected by permanent hearing impairment. This emphasises how meaningful this approach is for the development of the deaf child. So far, there is very little evidence about this approach in Italy, and there are still some barriers to its practical management. The aim of this paper is to report the results of a strategic analysis, which identifies the strengths, weaknesses, opportunities and threats of the family empowerment process during early auditory diagnosis and rehabilitation. The audiology programme should have the goal to offer information and support to families in order to achieve a conscious decision about the use and type of auditory prosthesis and rehabilitation choice within three months after audiologic diagnosis. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children", a group of professionals identified three main recommendations that can be useful to foster the natural communicative development of the child by strengthening the therapeutic alliance and empowerment of the family. The recommendations obtained with this analysis can help to develop new Italian guidelines with the aim to foster natural communicative development of the child by strengthening the therapeutic alliance and empowerment of the family.